Drug treatment of toxoplasmic encephalitis in acquired immunodeficiency syndrome. - Winstanley, P. (BMJ Group, 1995)
Toxoplasma gondii is a ubiquitous parasite, which causes several serious diseases. Until the AIDS pandemic, toxoplasmic encephalitis was largely confined to the pharmacologically immune-suppressed and to cases of congenital transmission. T gondii is now one of the more commonly encountered opportunistic pathogens of advanced AIDS.